2019
DOI: 10.22159/ajpcr.2019.v12i3.30894
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Attenuates Acute Gentamicin-Induced Nephrotoxicity in Sprague-Dawley Rats: The Potential Antioxidant and Anti-Inflammatory Effects

Abstract: Objectives: Nephrotoxicity is a renal-specific situation in which the excretion of toxic metabolites is reduced due to toxic agents and drugs. Gentamicin is an antibiotic belongs to aminoglycoside group which may induce nephrotoxicity due to induction of oxidative stress. Pomegranate is a component of the traditional medicine called Punica granatum with significant nephron-protective effect. Therefore, the objective of the present study was to evaluate the nephronprotective effect of pomegranate in gentamicin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
(11 reference statements)
2
11
0
Order By: Relevance
“…As well, induction of oxidative stress is the most important pathway of GIN leading to lipid peroxidation and tubular damages. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…As well, induction of oxidative stress is the most important pathway of GIN leading to lipid peroxidation and tubular damages. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…[18] However, in vitro and in vivo studies demonstrated that uninterrupted administration of nephrotoxic agents in rats for 7 days' result in time-dependent increase in both KIM-1 and NGAL serum levels before the initiation of renal proximal tubules damage suggesting that both KIM-1 and NGAL are sensitive in the detection of molecular renal damage. [19]…”
Section: Discussionmentioning
confidence: 99%
“…Some medications have multiple effects on renal function (9)(10)(11). Drugs are responsible for ∼20% of nephrotoxicity (12). In the large community of AKI-associated medications, antibiotics and other antimicrobials are well-known contributors to structural and functional renal dysfunction (13).…”
Section: Introductionmentioning
confidence: 99%